Orientação da marca do empreendedor e percepções do cliente sobre o posicionamento de marca de uma pequena empresa - Menezes, Brenda Cortez de (Brasil, 2024)
Brand positioning refers to a strategic set of actions designed to add value to the consumer. Given this context, this study aims to analyze the brand positioning of a small business regional urban fashion company in the Amazon, comparing the vision sought by the entrepreneurs with the perception of the consumer public. Qualitative and exploratory in nature, the research is focused on understanding the experiences and perceptions of customers in relation to a small Amazonian urban fashion company, and the positioning desired by the company's owners. Data collection used focus group techniques with customers and in-depth personal interviews with owners. The analysis included transcribing the statements and coding the data into three thematic categories: purchasing decision criteria, brand positioning perceived by customers and brand positioning desired by the brand. The results revealed that there is alignment between customer expectations and the positioning desired by managers, especially in terms of regionality.